(untitled) (Scientific journal of the Fergana State University, 2025)
This article discusses the possibility of motivating a person to perform any action through mind control, and psychologists and sociologists argue that manipulation is a type of psychological influence that is used to achieve unilateral gain by indirectly encouraging a person to perform certain actions. The word manipulation comes from Latin and means hand movement. The reforms being implemented in the social sphere are discussed.